PENGARUH KEPERCAYAAN DAN KEMUDAHAN MENGGUNAKAN E-COMMERCE TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Citra Suci Mantauv (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
The purpose of this study was to determine the influence of trust and ease of use using e-commerce online purchasing decision. Technique sampling in this study based on techniques Purposive sampling. It was used the analysis of multiple linear regression. The results showed that significantly influence the trust of online purchasing decisions, ease of use significantly influence purchasing decision online, and trust of use e-commerce ease significantly insfluence purchasing decisions online simultaneously